DEVELOPING ECONOMIC RELATIONS IN THE BORDER STRIP BETWEEN IRAQ AND IRAN - Researcher: Najwa Sadiq Ismail Al-Qanati (Scholars Digest Publishing, 2024)
The aim of this study is to identify the opportunities available on the border strip and determine priorities for development strategies for the border areas between Iran and Iraq, with an interest in using the opinion of experts and specialists in collecting survey data. The statistical population for the research was 10 specialists and experts in the border areas between Iran and Iraq, who were identified using the snowball method and whose opinions were used to obtain the required information. The geographical area for research was the border strip between Aryan and Iraq from the city of Al-Faw in the south of the two countries to Alan Point in the cities of Ashnoy in Iran and Soran in Iraq. The time scope of the research was February 1401 and in terms of the scope of the subject, economic development and strategic management were the basis of the study. The method of data analysis and strategy extraction was to use the SWOT model and the Quantitative Strategic Planning Matrix (QSPM). The results of the research on extracting strategies for developing the border strip in order of priority were as follows: A) More interaction between Iran and Iraq in order for Iran to participate in establishing and rebuilding Iraq’s infrastructure. b) Two countries aligned with preferential trade agreement arrangements between Iran and Iraq. c) Using different and varied means of transportation in cross-border trade. D) Solving the security problem on the border between the two countries. e) Expanding frontier markets. f) Rapid increase in cultural relations, religious and health tourism and education; g) Increasing the circulation of manufactured goods and their diversity in border areas; h) Investment in border areas.
Keywords: development of border areas, preferential trade, border market, comprehensive relations.